Expression of NM23 and tenascin in invasive ductal carcinomas of the breast - (:unkn) unknown (My University, 2002)
OBJECTIVE: In this series of ductal carcinoma of the breast, immunoexpression of antimetastasis gene nm23 and tenascin was examined and the role in prognosis was investigated by correlation with the tumour grade and stage, and ER/PR immunoexpression. MATERIAL AND METHODS: In this study 27 ductal carcinomas of the breast were analysed for expression of tenascin and nm23 antimetastasis genes by immunohistochemistry. RESULTS: The results of our study revealed a statistically significant correlation between nm23-H1 immunoexpression and lymph node metastasis. We also found a statistically significant correlation between tenascin and nm23-H1 immunoexpression. Our results suggest that tenascin limits tumour spread. CONCLUSION(S): Antimetastasis gene expression can be used in predicting lymph node metastasis in ductal carcinomas of the breast.
Keywords: Adult; Female; Humans; Middle Aged; Prognosis; Biomarkers, Tumor; Aged; Immunohistochemistry; Lymphatic Metastasis; Transcription Factors; Neoplasm Staging; Tenascin; Breast Neoplasms; Carcinoma, Ductal, Breast; Monomeric GTP-Binding Proteins; NM23 Nucleoside Diphosphate Kinases; Nucleoside-Diphosphate Kinase